Parámetros agronómicos del tomate (Solanum lycopersicum L.) inoculado con “Candidatus Liberibacter solanacearum” y tratados con fosfitos: Agronomic parameters of tomato (Solanum lycopersicum L.) inoculated with “Candidatus Liberibacter solanacearum” and treated with phosphites - Roque Enriquez, Alberto; Delgado-Ortiz, Juan Carlos; Beltrán-Beache, Mariana; Ochoa-Fuentes, Yisa; Cerna-Chávez, Ernesto (Ecosistemas y Recursos Agropecuarios, 2021)
The disease permanente del tomate or zebra chip associated by “Candidatus Liberibacter solanacearum” (Ca. L. solanacearum), is of great importance in the tomato producing regions of Mexico, which causes losses of between 60 and 100% of the production. The objective of this research was to evaluate the effect of six phosphites (FOS), salicylic acid and acibenzolar s-methyl on the growth of the tomato crop and the severity of Ca. L. solanacearum. Tomato plants were infected with Ca. L. solanacearum by confinement with adults of B. cockerelli carrying this bacterium. In response, the decrease in the severity of the disease and nine agronomic parameters were evaluated. Phosphite spraying reduced the severity of the symptoms of the disease caused by Ca. L. solanacearum, improving the variables plant height, fruit weight, plant weight and root weight. On the other hand, the spraying of salicylic acid and acibenzolar s-methyl did not reduce the effects of the disease in the tomato crop.